Quality indicators of Physical therapy practice in Pakistan - Roohi Abbas, Samreen Sadiq, Hina Gul, Sidra Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Quality refers to the extent of superiority or excellence of something when compared with other things of similar characteristics1. During this era of quality enhancement, more and more emphasis is now being given to raise the standards of providing quality services in health care1. One possible way of ascertaining high quality service provision is by “measuring” the quality of services being provided, as this will help to identify either good or bad providers of services that is the health care practitioners2. This has gained much importance globally and a lot of work has been done by the researchers and stakeholders to measure and to standardize the quality of health care services2.